Peri-implantitis: A Classification Update - Shrestha, Rejina; Bhochhibhoya, Amar Bhochhibhoya (Nepal Journal of Health Sciences, 2021)
The cases of peri-implantitis are soaring rapidly in the current scenario. It is very important to have adequate knowledge about the etiology, pathogenesis, clinical features, radiological features, and treatment of peri-implantitis. In this context, the classification of the disease is of utmost importance for planning and execution of the treatment. Various classifications have been proposed over the years and with each classification, more information is being added and there is a lack of universal acceptance of a single classification. Clinical errors may be anticipated due to miscommunication and misguidance. Thus, it is important to sensitize the clinicians about different classification systems. This review attempts to compile and critically analyze existing classification systems of peri-implant diseases.Keywords: Dental implants; diagnosis; peri-implantitis.